2019
DOI: 10.1002/ese3.530
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on a novel support system for controlling roadway deformation in underground coal mines

Abstract: Roadway stability in extremely soft coal mass is a typical challenge in deep underground mines, as the most widely adopted support structure such as rock bolting, compound support system normally fails. This paper proposed a novel prereinforcement method for coal roadway, that is, jet grouting (JG) technique, to improve the quality of surrounding soft coal mass and form a stable support structure namely jet grouted coalcrete. The field and laboratory tests were conducted for evaluating the applicability of JG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…Grouting as a reinforcement method can enhance the physical and mechanical properties of coal mass, which was confirmed by many successful engineering cases [40][41][42][43]. Therefore, the pre-grouting technique (e.g., horizontal jet grouting [44,45]) and delayed grouting are additionally proposed to control the time-dependent deformation of such a soft coal roadway.…”
Section: Discussion and Suggestionsmentioning
confidence: 93%
“…Grouting as a reinforcement method can enhance the physical and mechanical properties of coal mass, which was confirmed by many successful engineering cases [40][41][42][43]. Therefore, the pre-grouting technique (e.g., horizontal jet grouting [44,45]) and delayed grouting are additionally proposed to control the time-dependent deformation of such a soft coal roadway.…”
Section: Discussion and Suggestionsmentioning
confidence: 93%
“…According to the field and laboratory test results, the diameter of the coalcrete column in this study is set to be 400 mm (shown in Figure A) and the mechanical parameters of coalcrete are given in Table . The Mohr‐Coulomb model is employed to coalcrete.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The cohesion and friction angle of coalcrete were obtained by shear tests (Figure 8b), and the deformation modulus and compressive strength were gained by uniaxial compressive tests (Figure 8c). Furthermore, according to the fitting functions mentioned in the literature [33,34], the empirical equations, reflecting the size effect on the strength properties of coalcrete, were further established. By using these equations, the mechanical parameters of coalcrete with 400 mm in diameter were determined and are given in Table 4.…”
Section: Mechanical Parameters Of Coalcretementioning
confidence: 99%
“…By using these equations, the mechanical parameters of coalcrete with 400 mm in diameter were determined and are given in Table 4. functions mentioned in the literature [33,34], the empirical equations, reflecting the size effect on the strength properties of coalcrete, were further established. By using these equations, the mechanical parameters of coalcrete with 400 mm in diameter were determined and are given in Table 4.…”
Section: Mechanical Parameters Of Coalcretementioning
confidence: 99%